Упростить выражение4сс-2-с-4^23aa+2-a+3^23y-1^2+6y8c+41-c^24ab+2a-b^23x+y^2-6xy3aa-2-a-3^2a-4^2-2a3a-4x-y^2-xx-2yaa-2b-a+b^2a-3a-7-2a3a-5x-2x+4-2×1+x2

Упростить выражение

4с(с-2)-(с-4)^2
3a(a+2)-(a+3)^2
3(y-1)^2+6y
8c+4(1-c)^2
4ab+2(a-b)^2
3(x+y)^2-6xy
3a(a-2)-(a-3)^2
(a-4)^2-2a(3a-4)
(x-y)^2-x(x-2y)
a(a-2b)-(a+b)^2
(a-3)(a-7)-2a(3a-5)
(x-2)(x+4)-2x(1+x)
2c(3c+4)-3c(2c+1)
3a(2a-1)-2a(4+3a)
(b+c)(b-c)-b(b-2c)
(a-c)(a+c)-c(3a-c)
a(a+5b)-(a+b)(a-b)
b(3a-b)-(a-b)(a+b)
(y+10)(y-2)-4y(2-3y)
(a-4)(a+9)-5a(1-2a)
(2b-3)(3b+2)-3b(2b+3)
(3a-1)(2a-3)-2a(3a+5)
(m+3)^2-(m-2)(m+2)
(a-1)^2-(a+1)(a-2)
(c+2)(c-3)-(c-1)^2
(y-4)(y+4)-(y-3)^2
(a-2)(a+4)-(a+1)^2
(b-4)(b+2)-(b-1)^2

    (b+c)(b-c)-b(b-2c) = c(2b - c)

    4ab+2(a-b)^2= 2(a - b)(a + b)

    3a(a+2)-(a+3)^2= 2a^2 - 9

     

    (2b-3)(3b+2)-3b(2b+3) = b - 6

     

     

     

    8c+4(1-c)^2= (2- c)^2

     

     

     

     

     

    (y+10)(y-2)-4y(2-3y) = 13y^2 - 20

    (c+2)(c-3)-(c-1)^2 = c - 7

     

     

    (x-y)^2-x(x-2y) = y^2

    (m+3)^2-(m-2)(m+2) = 6m + 13

    2c(3c+4)-3c(2c+1) = 5c

    (b-4)(b+2)-(b-1)^2 = b^3 + 3b^2 - 2b - 7

    (a-c)(a+c)-c(3a-c) = a(a - 3c)

    (a-4)^2-2a(3a-4) = 16 - 5a^2

     

    (3a-1)(2a-3)-2a(3a+5) = 3(1 - 7a)

    3a(a-2)-(a-3)^2 = 2a^2 - 9

     

     

     

     

    a(a+5b)-(a+b)(a-b) = b(b - 5a)

     

     

    (a-4)(a+9)-5a(1-2a) = 11a^2 - 36

    (x-2)(x+4)-2x(1+x) = -8 - x^2

     

    3(x+y)^2-6xy= 3(x^2 + y^2)

     

    3a(2a-1)-2a(4+3a) = -11a

    b(3a-b)-(a-b)(a+b) = a(3b - a)

     

     

  • (a-3)(a-7)-2a(3a-5) = 21 - 5a^2

    3(y-1)^2+6y= 3(y^2 - 1)

  • 4с(с-2)-(с-4)^2= 3с^2 - 16

    (a-2)(a+4)-(a+1)^2 = a^2 + 2a - 7

     

    a(a-2b)-(a+b)^2 = b(-4a - b)

     

     

     

    (a-1)^2-(a+1)(a-2) =3 - a

     

    (y-4)(y+4)-(y-3)^2 = 6y - 25